Post-Soviet transformation of rural space in Ukraine: from polarization to decentralization - Mykola Baranovskyі (Časopis Socìalʹno-Ekonomìčnoï Geografìï. Часопис соціально-економічної географії)
The post-Soviet transformation of the rural space of Ukraine was caused by the change in the economic system in the country in the early 90s of the 20th century. The main territorial consequence of the post-Soviet transformation of the agrarian sphere was the intensification of the rural space polarization, which manifests itself at various hierarchical levels and encompasses its main subsystems - agriculture and rural society. The reflection of polarization in the rural economy is an increase in the concentration of agricultural production in areas that have better natural conditions for their development, as well as in suburban areas. In the northern regions of Ukraine, polarization is manifested through the "better-worse natural conditions" for the development of agrarian production, in the south - along the "suburban areas-peripheral territories". The leaders in general and per capita indexes of agricultural products manufacture, rates of its growth in recent years are Vinnytsia, Poltava, Dnipropetrovsk and Cherkasy regions. Under the influence of market factors and in accordance with the general laws of the rural areas evolution, there is also a redivision of rural population. In the regions of Ukraine it concentrates mainly around large and medium-sized cities, in rural communities that are directly adjacent to them. The regional centers "support" about 12-14% of the rural population of their region, the middle-sized - 6-8%. In rural communities around large and medium-sized cities, between 35 and 50% of the rural population of the respective administrative districts is concentrated. They are also distinguished by the high population density, the slow pace of reduction of the rural population as compared with the peripheral communities, and, in some cases (around Kyiv and most of the region centers of the country) even by increasing its size. In general, the dependence is clearly traced - the larger the city, the greater the concentration zone of rural population it forms. The increase of the rural space polarization causes a number of problems; the most significant among them is the degradation of peripheral territories. Decentralization of governance, in particular the creation of amalgamated territorial communities, is an important tool for solving the problems of rural areas. Community centers should be the pillars of growth in rural areas. Due to changes in the tax system, they received significant financial resources, primarily through revenue from personal income tax. However, most of the newly created communities are not financially autonomous, and, therefore, their impact on the revival of rural areas remains insufficient.